Simple artificial training device for respiratory muscle strength and lung volumes in healthy young male and female subjects: A pilot study - Jirakrit Leelarungrayub (2018)
© 2016 Elsevier Ltd Objective The aim of this study was to evaluate the efficiency of a simple artificial device for respiratory muscle strength training and lung volumes using either combined or non-combined exercise with elastic bands in healthy young participants. Methods Forty healthy young participants (20 male and 20 female) aged 19–24 years old were randomized into two main experiments with four sub-groups; (1) artificial device (n = 10) & standard device (n = 10) training, and (2) artificial device training combined with elastic band (EB) exercise (n = 10) & standard device training combined with EB (n = 10) exercise. Respiratory muscle strength with maximal peak inspiratory pressure (PImax), and lung volumes; tidal volume (TV), inspiratory reserve volume (IRV), expiratory reserve volume (ERV) and vital capacity (VC) were evaluated before and after training once daily for 3 weeks. Moreover, the peak dyspnea score and vital sign parameters were compared between the experimental groups after final training. Results All parameters had no statistical differences (p > 0.5) between the training devices alone and those combined with EB exercise prior to any experiments. Results from the first experiment showed that training with an artificial device increased all parameters (PImax, VC, IRV, ERV) significantly (p < 0.05), except for TV, when compared to pre training results, which were the same as those in the standard device training group. No statistical difference was shown between these groups after the training period had been performed. Furthermore, results of applying artificial device training combined with EB exercise showed a significant increase in all parameters, except for TV, and they were the same as the increased results in training with the standard device combined with EB exercise. There was no significant difference of data between these groups after the training period. Finally, the results of peak dyspnea score and all vital sign parameters from using the artificial device, with or without EB exercise, showed no statistical difference when compared to use of the standard device. Conclusion This study proposed that a simple artificial device can be used to train the respiratory muscle with or without elastic band exercise in healthy young subjects.